Human trafficking and the effectiveness of asylum policies - Jenny Monheim (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 2008)
We investigate the effects of restrictive asylum policies on the number and group composition of asylum seekers. We model the choices of refugees and traffickers about whether to migrate and to apply for asylum. Counter-intuitively, restrictive asylum policies do not lead to a reduction in the inflow of refugees or to a better selection of asylum seekers. Instead, we show that under conditions outside the control of policy makers these policies can increase the number of asylum claims and the number of refugees working in slave-like conditions and prevent some of those most in need of protection from accessing it.
Keywords: D78; F22; K49; 330; Asylum policy; Illegal immigration; Human trafficking